Representasi Komunikasi Interpersonal dalam Bertetangga - Muhammad Faizal Ramdhan; Askurifa'i Baksin (UNISBA Press, 2024)
Abstract. This research is motivated by film as a mass communication medium that can represent social reality. With film, audiences can see a reality that occurs in other environments. Interpersonal communication that occurs in neighbors can be represented in the film. The film that will be analyzed in this study is the film